2016
DOI: 10.1111/eci.12641
|View full text |Cite
|
Sign up to set email alerts
|

Brain change trajectories that differentiate the major psychoses

Abstract: Background Bipolar disorder and schizophrenia are highly heritable, often chronic and debilitating psychotic disorders that can be difficult to differentiate clinically. Their brain phenotypes appear to overlap in both crosssectional and longitudinal structural neuroimaging studies, with some evidence to suggest areas of differentiation with differing trajectories. The aim of this review was to investigate the notion that longitudinal trajectories of alterations in brain structure could differentiate the two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 120 publications
0
17
0
Order By: Relevance
“…Accordingly, brain volume constraints in SZ are better explained as a combination of early neurodevelopmental disturbance and disease progression [Haijma et al, 2013]. Longitudinal studies have suggested that the SZ brain entails a disorder-specific trajectory of morphological changes (compared with other psychotic conditions), characterized by a progressive grey matter loss confined to frontotemporal cortical regions [De Peri et al, 2012;Liberg et al, 2016]. Studies in childhood onset SZ have revealed a reduced cerebral volume and cortical thickness during childhood and adolescence, which level off in adulthood, along with deficits in local connectivity and increased long-range connectivity [Baribeau and Anagnostou, 2013].…”
Section: Brain Anomalies and Dysfunctionsmentioning
confidence: 99%
“…Accordingly, brain volume constraints in SZ are better explained as a combination of early neurodevelopmental disturbance and disease progression [Haijma et al, 2013]. Longitudinal studies have suggested that the SZ brain entails a disorder-specific trajectory of morphological changes (compared with other psychotic conditions), characterized by a progressive grey matter loss confined to frontotemporal cortical regions [De Peri et al, 2012;Liberg et al, 2016]. Studies in childhood onset SZ have revealed a reduced cerebral volume and cortical thickness during childhood and adolescence, which level off in adulthood, along with deficits in local connectivity and increased long-range connectivity [Baribeau and Anagnostou, 2013].…”
Section: Brain Anomalies and Dysfunctionsmentioning
confidence: 99%
“…Loss of gray matter, due to loss of neurons and thinning of the neuropil, has been described in both schizophrenia and bipolar disorder . The loss of gray matter in schizophrenia has been reported in many brain areas, including bilateral insular cortex, anterior cingulate cortex, left parahippocampal gyrus, left middle frontal gyrus, postcentral gyrus and thalamus .…”
Section: Discussionmentioning
confidence: 99%
“…The loss of gray matter in schizophrenia has been reported in many brain areas, including bilateral insular cortex, anterior cingulate cortex, left parahippocampal gyrus, left middle frontal gyrus, postcentral gyrus and thalamus . Bipolar patients, in general, manifest less gray matter loss compared to normal controls, than do schizophrenia patients, with loss concentrated in cingulate cortical areas . Gray matter loss in schizophrenia and bipolar disorder has been attributed to excessive pruning and inflammation during early development, as well as during the prodromal period, with genetic factors and stress considered to be the major basis for the loss of gray matter .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations